2004
DOI: 10.1515/jpm.2004.138
|View full text |Cite
|
Sign up to set email alerts
|

β2-adrenergic receptor gene polymorphisms and pregnancy outcome

Abstract: At codon 16 of the beta2-AR gene, maternal Arg-16 homozygosity protects against, and Gly-16 predisposes to spontaneous preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 20 publications
0
31
1
7
Order By: Relevance
“…Associations were also found between the ␤ 2 -adrenergic receptor (ADRB2) polymorphisms and preterm labor (20,21). Moreover, Landau et al (22) showed that ADRB2 Arg16 homozygosity improves pregnancy outcome after ␤(2)-agonist tocolysis.…”
Section: Discussionmentioning
confidence: 98%
“…Associations were also found between the ␤ 2 -adrenergic receptor (ADRB2) polymorphisms and preterm labor (20,21). Moreover, Landau et al (22) showed that ADRB2 Arg16 homozygosity improves pregnancy outcome after ␤(2)-agonist tocolysis.…”
Section: Discussionmentioning
confidence: 98%
“…[5][6][7][8] Some observations suggest the existence of a genetic predisposition to PRM and PD, [9][10][11][12][13][14] and several genetic polymorphisms have been proposed as risk factors. [13][14][15][16][17][18][19] Previous studies have investigated the association between reninangiotensin system (RAS) polymorphisms and pregnancy complications, such as stillbirth, abortion, pre-eclampsia, and hypertension. [20][21][22][23][24] Some of these entities are considered risk factors for PD.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal ADRB2 genotype has been investigated in relation to risk for pre-term labor and birth, with the Gly16 51,52 and Glu27 53 alleles being associated with higher risk, whereas autism has been associated with premature birth in some [54][55][56] though not all 57,58 studies. The observed association between Glu27 homozygous genotype and autism, therefore, could possibly be explained by maternal genotype, mediated through prematurity.…”
Section: Discussionmentioning
confidence: 99%